2009
DOI: 10.1007/s00268-009-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Launching Surgery at the District Level in Niger

Abstract: Background In 2005, the Ministry of Health in association with the Faculty of Medicine of Niamey decided to launch surgery at the district hospital (DH) level as part of the health strategy for the country. Surgical procedures were provided by general practitioners who received 12 months of training in basic surgery. Methods Whereas the initiative was launched nationwide, we chose randomly to study the region of Dosso during a 1-year time period of January 2007 to December 2007 in the three district hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 17 publications
4
70
0
Order By: Relevance
“…Skilled manpower for health care is a serious problem in developing countries. World Health Organization (WHO) reported that Africa contributes about 25 % of the world's burden of disease but possessed only 1.3 % of qualified health professional [1,2]. The lack of human resources to perform surgery in sub-Saharan Africa is due to the brain drain to Europe and a shortage of teaching and training facilities adapted to the emergency surgery needs [3].…”
Section: Human Resourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…Skilled manpower for health care is a serious problem in developing countries. World Health Organization (WHO) reported that Africa contributes about 25 % of the world's burden of disease but possessed only 1.3 % of qualified health professional [1,2]. The lack of human resources to perform surgery in sub-Saharan Africa is due to the brain drain to Europe and a shortage of teaching and training facilities adapted to the emergency surgery needs [3].…”
Section: Human Resourcesmentioning
confidence: 99%
“…Based on lessons from the failure of the 1995 program, the Faculty of Medicine agreed to increase the number of trainees and to improve teaching methods. The certificate called "Capacity of District Surgery" was created for students who were government physicians who finished 12 months of training [2]. The diploma of district surgery also provided a bonus on their annual salary as additional incentive.…”
Section: History Of Rural Surgery In Nigermentioning
confidence: 99%
See 3 more Smart Citations